Enzymatically enhanced ultrastructure expansion microscopy unlocks expansion of in vitro Toxoplasma gondii cysts - Kseniia Bondarenko; Floriane Limoge; Kayvon Pedram; Mathieu Gissot; Joanna C. Young (mSphere)
ABSTRACT Expansion microscopy (ExM) is an innovative approach to achieve super-resolution images without using super-resolution microscopes, based on the physical expansion of the sample. The advent of ExM has unlocked the detail of super-resolution images for a broader scientific circle, lowering the cost and entry skill requirements for the field. One of its branches, ultrastructure expansion microscopy (U-ExM), has become popular among research groups studying apicomplexan parasites, including the acute stage of Toxoplasma gondii infection. Here, we show that the chronic cyst-forming stage of Toxoplasma, however, resists U-ExM expansion, impeding precise protein localization. We then solve the in vitro cyst’s resistance to denaturation required for successful U-ExM. As the cyst’s main structural protein CST1 contains a mucin domain, we added an enzymatic digestion step using the pan-mucinase StcE prior to the expansion protocol. This allowed full expansion of the cysts in fibroblasts and primary neuronal cell culture without disrupting immunofluorescence analysis of parasite proteins. Using StcE-enhanced U-ExM, we clarified the localization of the GRA2 protein, which is important for establishing a normal cyst, observing GRA2 granules spanning across the CST1 cyst wall. The StcE–U-ExM protocol allows accurate pinpointing of proteins in the bradyzoite cyst, which will greatly facilitate investigation of the underlying biology of cyst formation and its vulnerabilities.IMPORTANCEToxoplasma gondii is an intracellular parasite capable of establishing long-term chronic infection in nearly all warm-blooded animals. During the chronic stage, parasites encapsulate to form cysts predominantly in neurons and skeletal muscle. Current anti-Toxoplasma drugs do not eradicate chronic parasites, leaving a reservoir of infection. The cyst is critical for disease transmission and pathology, yet it is harder to study, with the function of many chronic-stage proteins still unknown. Ultrastructure expansion microscopy, a new method to overcome the light microscopy’s diffraction limit by physically expanding the sample, allowed in-depth studies of acute Toxoplasma infection. We show that Toxoplasma cysts resist expansion using standard protocol, but an additional enzymatic digestion with the mucinase StcE allows full expansion. This protocol offers new avenues for examining the chronic stage, including precise spatial organization of cyst-specific proteins, linking these locations to morphological structures, and detailed investigations of components of the durable cyst wall.